Stingless Honeybee’s Rare Sugar and PCSK 9 - LDLR Interaction, A New Hope for Hormone Dependent Breast Cancer Patients – An In-silico Study - Prakash Vaithyanathan (International Journal of Cheminformatics, 2025)
Hypercholesterolemia is a lipid disorder characterized by elevated levels of low-density lipoprotein (LDL), commonly known as "bad" cholesterol. This condition is a significant risk factor in the development and progression of hormone-dependent breast cancer, as well as in the emergence of resistance to hormonal therapy. One of the key regulators of cholesterol metabolism is the proprotein convertase subtilisin/kexin type-9 (PCSK9) protein, which facilitates the degradation of the LDL receptor (LDLR) after binding to it. The reduction of LDL receptors leads to increased circulating LDL cholesterol levels, thereby exacerbating hypercholesterolemia. Recent studies suggest that targeting the PCSK9-LDLR interaction, often referred to as the PCSK9-LDLR axis, may provide a promising strategy for managing hypercholesterolemia while also mitigating the progression of hormone-dependent breast tumors. Small molecule inhibitors that disrupt this interaction have emerged as potential therapeutic agents in both cardiovascular and cancer research. Notably, docking studies have now identified trehalulose, a rare and non-toxic sugar present in the honey produced by stingless honey bees, as a potential candidate for lowering LDL cholesterol levels. By enhancing LDL clearance, trehalulose could offer significant benefits to breast cancer patients globally, presenting a novel and natural approach to cholesterol management and cancer prevention.
Keywords: Hypercholesterolemia; LDLR; PCSK9; Trehalulose; bad cholesterol; hormone dependent breast cancer; stingless honey bee